Developing analytical exposition reading materials on healthy life for the student of nursing assistant study program of vocational high school - Desi Ramasari; Rita Inderawati; Soni Mirizon; Karen Ferreira-Meyers (Sriwijaya University Learning and Education International Journal, 2024)
This study aimed to develop valid, appropriate, and potentially effective analytical exposition reading materials on healthy living for tenth-grade students. This study was conducted based on development research, which consists of four phases: analysis, design, evaluation, and revision. The data were gathered via questionnaires, semi-structured interviews, and a reading comprehension test. The data were quantitatively and qualitatively analyzed. A formative evaluation was conducted to ascertain the reading materials' validity, practicality, and potential impact. The result of the validity reading materials was a very high validity of 4.54 when assessed by content, instructional design, and media experts. Then, the result of the reading materials' practicality was very high in one-on-one (4.23) and small group (4.05) evaluations. The field test result was 85.57%, indicating that the generated reading materials had a high potential impact. As a result, the developed reading resources might be utilized as supplements to teach English reading material to tenth-grade students.